2014
DOI: 10.1111/ane.12289
|View full text |Cite
|
Sign up to set email alerts
|

Eight-year follow-up of patients with myasthenia gravis after thymectomy

Abstract: Extended thymectomy combined with immunotherapy is a preferred treatment with a satisfactory long-term remission rate. Patients with non-thymomatous myasthenia gravis have a much more promising prognosis than the patients with thymomatous myasthenia gravis. However, appropriate caution must be taken to discontinue pharmaceutical therapy as relapse remains a major concern after a patient who has already undergone thymectomy becomes symptom-free.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 33 publications
4
15
0
2
Order By: Relevance
“…We showed that the MG patients with nonthymomatous pathology were 2.17 times more likely to achieve remission compared with the patients with thymomatous pathology. This result is consistent with results from previous studies that included large numbers (>100) of patients . However, other studies have found that nonthymomatous pathology is not a prognostic factor .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We showed that the MG patients with nonthymomatous pathology were 2.17 times more likely to achieve remission compared with the patients with thymomatous pathology. This result is consistent with results from previous studies that included large numbers (>100) of patients . However, other studies have found that nonthymomatous pathology is not a prognostic factor .…”
Section: Discussionsupporting
confidence: 91%
“…This result is consistent with results from previous studies that included large numbers (>100) of patients. 4,6,15 However, other studies have found that nonthymomatous pathology is not a prognostic factor. 5,[16][17][18] This discrepancy may be a result of differences in participants, followup times, or sample sizes.…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of MG was significantly different in type B2 thymoma compared with that in other types of thymoma. In the 38 patients that had thymoma with MG, muscle weakness relief following surgery was 77.8%, which is similar to the 81.1% reported by Yu et al (29). However, 1 out of 66 (1.5%) patients without preoperative MG developed postoperative MG in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…However, the risk of generalization from OMG to generalized MG (GMG) do exist for part of patients, and certain treatment might delay or prevent the onset of GMG (1). Besides, the presence of OMG before operation was one of the favorable factors according to a large sample retrospective study (34). Therefore, 8 cases of MGFA classes I were enrolled in our study, among which 5 cases achieved CSR and all of the 8 patients achieved significant improvement till the last follow up.…”
Section: Discussionmentioning
confidence: 99%